2020
DOI: 10.1002/advs.202000649
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness of HIV‐1 Mimicking Polymer Nanoparticles Modulates Ganglioside‐Mediated Cellular Uptake and Trafficking

Abstract: The monosialodihexosylganglioside, GM3, and its binding to CD169 (Siglec‐1) have been indicated as key factors in the glycoprotein‐independent sequestration of the human immunodeficiency virus‐1 (HIV‐1) in virus‐containing compartments (VCCs) in myeloid cells. Here, lipid‐wrapped polymer nanoparticles (NPs) are applied as a virus‐mimicking model to characterize the effect of core stiffness on NP uptake and intracellular fate triggered by GM3‐CD169 binding in macrophages. GM3‐functionalized lipid‐wrapped NPs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 97 publications
3
50
0
4
Order By: Relevance
“…There are several nanoparticle parameters that influence their uptake into the cells [44][45][46][47][48][49][50][51], and some recent studies exemplifying these are shown in Table 1. A brief overview of NP physicochemical properties and their impact on internalization is described below.…”
Section: Role Of Physico-chemical Properties Of Nps In Cell Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…There are several nanoparticle parameters that influence their uptake into the cells [44][45][46][47][48][49][50][51], and some recent studies exemplifying these are shown in Table 1. A brief overview of NP physicochemical properties and their impact on internalization is described below.…”
Section: Role Of Physico-chemical Properties Of Nps In Cell Uptakementioning
confidence: 99%
“…Quantifying the effect of NP elasticity on cellular uptake is challenging because of experimental difficulties in measuring the micro-and nano-scale mechanical properties of NPs [51,108]. One of the problems in the study of the elasticity effects on the NP endocytosis is the fact that many physiochemical properties of NPs are strongly related to each other.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Solid nanoparticles consist of polymeric, metallic, or semiconducting materials, which exhibit lower surface mobility compared with biological lipid membranes. Contrary to metallic and semiconducting nanoparticles, polymeric nanoparticles confer tunable mechanical modulus, which allows the emulation of various viral core stiffness which is correlated with viral maturation state and infectivity (Kol et al, 2007 ; Eshaghi et al, 2020 ). In addition, several pH-responsive self-assembled polymeric nanoparticles can be disassembled in low pH environments such as tumor region or endolysosome in the cell, providing targeted release of the cargo (Liao et al, 2018 ; Pan et al, 2018 ).…”
Section: Solid Nanoparticle Probes For Protein-carbohydrate Interactionsmentioning
confidence: 99%
“…[ 7 ] Optimization of physical parameters was also investigated to improve drug delivery of nanoformulations. These studies showed that nanoformulation physical properties such as size, [ 8 ] shape, [ 9 ] surface chemistry, [ 10 ] and elasticity [ 11 ] play critical roles in regulating nano‐bio interactions including cell uptake, blood circulation, tumor penetration, and accumulation. Understanding how physical properties affect underlying biomechanisms should shed light on the design of drug delivery vectors with higher efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The elasticity is the ability of an object resist deformation caused by stress and to return to its original state when the stress is removed. [ 12 ] The factors that may potentially impact the elasticity of nanoformulations include the intrinsic property of materials, [ 13 ] crosslinking density, [ 14 ] thickness, [ 15 ] polymer volume fraction [ 11e ] and the encapsulated components [ 11 , 16 ] (Table S1 , Supporting Information). To date, how exactly elasticity of nanoformulations affect their biological performance is still unclear or even debatable.…”
Section: Introductionmentioning
confidence: 99%